Causal Factors Of Frenemy On Emily And Stephanie In Jessica Sharzer’s A Simple Favor Movie Script - Shafa Camila, Myrilla; Hariyono (Gudang Jurnal Multidisiplin Ilmu, 2025)
This study examines the frenemy relationship between Emily and Stephanie in A Simple Favor. Their friendship is complex, blending admiration, competition, and manipulation. Stephanie looks up to Emily but also struggles with insecurity, while Emily enjoys maintaining control over Stephanie. Using a qualitative method, this research identifies key factors contributing to their frenemy dynamic, including social comparison, insecurity, past betrayals, and cultural expectations. The findings reveal that their relationship is shaped by both emotional dependence and hidden rivalry, leading to an unstable and toxic bond. Finally, the study highlights how friendships can mask deeper conflicts, where trust and betrayal coexist.